Bangunan Pembentukan Teori Konstruksi Sosial Peter L Berger: Teori Pembedah Realitas Ganda Kehidupan Manusia - Nurkhalis Nurkhalis (Jurnal Community, 2018)
AbstractThis article examines two realities of life experienced by humans in living. These two realities are subjective and objective, both of which have a high power of study when combined. As the development of phenomena or social problems increasingly complex, the presence of Social Construction theory becomes a bridge to see the social situation in the two sides of the subjective and objective. As the sociologists struggle arguing for subjective and objective dominance, the Social Construction theory takes its position as peacemaker by giving portions on both sides that are equally important. Therefore, it is appropriate that the Social Construction theory is categorized into the critical theory of a set of tools closer to the social reality for observing the social dynamic and social static.Keywords: Subjective, Objective, Social Construction theory, Social Dynamic, Social Static